Marketing Evaluation of Personnel Building Companies (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article deals with the problematic issues of application of the marketing assessment in the formation and use of personnel potential of the enterprise. Formulated the theoretical basis for the definition and interpretation of the personnel potential of the enterprise. The directions and methods of marketing evaluation of personnel potential.
Keywords: human resources, marketing, marketing evaluation, marketing staff